Review: Alternative Placement of Penile Prosthesis Reservoir and AUS Pressure Regulating Balloon. Issue 1 (26th November 2014) - Reznicek, Daniel G.; Bryson, Richard; Kramer, Andrew C.
Abstract Introduction Ectopic placement of prosthetic balloons and reservoirs in urological surgery has gained popularity, and early experience suggests that such placement is safe and efficacious. We review the artificial urinary sphincter (AUS) pressure regulating balloon (PRB) and inflatable penile prosthesis (IPP) reservoir placement and the factors relating to ectopic vs. traditional paravesical placement of these devices. Methods Articles from peer‐reviewed journals, abstracts, and surgeons' series of outcomes form the basis for this review. Relevant mechanical function of devices and pertinent anatomy is reviewed. Main Outcome Measures To review the current data regarding ectopic and conventional reservoir placement for the AUS and IPP. Results Traditional and ectopic placements of the AUS PRB and IPP reservoir have been shown to be safe and effective. There are well‐documented risks associated with both traditional and ectopic approaches, and these risks must be weighed in the context of a specific clinical scenario and surgeon comfort. Conclusion Traditional and ectopic placement of prosthetic balloons and reservoirs should be guided by patient characteristics and surgeon experience. Our early experience is in agreement with that of others in that ectopic placement of these devices appears to be a viable alternative in the appropriately selected patient and may be a technically easy procedure to learn for the experienced prosthetic surgeon. Reznicek DG, Bryson R, and Kramer AC. Review: Alternative placement of penile prosthesis reservoir and AUS pressure regulating balloon. Sex Med Rev 2015;3:48–55.